2019
DOI: 10.1109/access.2019.2935751
|View full text |Cite
|
Sign up to set email alerts
|

Design of a New Seven-Dimensional Hyperchaotic Circuit and Its Application in Secure Communication

Abstract: In the fields of physics, mathematics, communication, control, biology, etc., chaos is widely used, and it plays an important role in modern science and technology. In this paper, a new sevendimensional hyperchaotic system is proposed and some related features of the hyperchaotic system are analyzed, including equilibrium stability, dissipation, bifurcation and Lyapunov exponent. The results show that the proposed hyperchaotic system exhibits hyperchaotic, chaotic, quasi-periodic and periodic dynamic behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…By establishing a mathematical model to analyze the combination of financial stability, not only can it help the macrocontrol of the financial system but also help the mitigation of the financial crisis through the study of the financial chaotic system control model. In recent years, significant progress has been made in the field of control [33][34][35][36][37][38][39][40]. Control algorithms have emerged endlessly, which have created favorable conditions for financial chaos control.…”
Section: Stability Is the Foundation Of Financial Developmentmentioning
confidence: 99%
“…By establishing a mathematical model to analyze the combination of financial stability, not only can it help the macrocontrol of the financial system but also help the mitigation of the financial crisis through the study of the financial chaotic system control model. In recent years, significant progress has been made in the field of control [33][34][35][36][37][38][39][40]. Control algorithms have emerged endlessly, which have created favorable conditions for financial chaos control.…”
Section: Stability Is the Foundation Of Financial Developmentmentioning
confidence: 99%
“…The work on applications of chaotic synchronization in secure communication has grown dramatically in recent years [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Developing control systems for synchronization of various chaotic systems has been one of the main focuses of prior works, aiming to improve security in communication.…”
Section: Introductionmentioning
confidence: 99%
“…Another work by [ 29 ] proposed the design of an Op-Amp-based analog circuit to obtain secure communication. The proposed analog circuit of the seven-dimensional chaotic system is designed and implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Chaotic and hyperchaotic systems have been used in most diverse contexts, including nonlinear identification [27]- [29], observation and control [30], [31], economy [32], [33], welding [34], [35], and secure communication [11], [21], [36], [37], [39]- [42]. In particular, chaos-based cryptography is a very active research topic in the literature, which is motivated by the pseudo-random behavior observed in chaotic systems.…”
Section: Introductionmentioning
confidence: 99%